Effectiveness of Soybean Pulp Oil as a Natural Preservative for Wagyu Beef: Impact on Moisture Retention and Nutritional Composition - Sugih Sunjaya; Dame Panggabean (Yayasan Darussalam Bengkulu, 2024)
This study evaluates the potential of soybean pulp oil as a natural preservative for Wagyu beef, specifically examining its effects on moisture retention, protein, and fat content. A Completely Randomized Design (CRD) was employed with four treatment groups (1%, 3%, 5%, and 7% soybean pulp oil) and five replications per treatment. The beef samples were stored for 12 hours at room temperature (30°C), and their chemical composition was analyzed for moisture, protein, and fat content. The results demonstrated a significant improvement in moisture retention in the 1% and 3% soybean pulp oil treatments, with average moisture levels ranging from 80% to 86%. However, no significant changes in protein and fat content were observed across treatments. These findings suggest that soybean pulp oil, which is rich in polyunsaturated fatty acids, can effectively preserve moisture in high-quality meats like Wagyu beef without affecting its protein or fat composition. The study highlights the potential of soybean pulp oil as a sustainable, natural alternative to synthetic preservatives in premium meat products. By utilizing a byproduct of soybean oil extraction, this approach also contributes to the circular economy and sustainable food production. The study’s findings have significant implications for the meat processing industry, especially in response to increasing consumer demand for natural food preservation methods. Further research is needed to explore the long-term effects of soybean pulp oil on other sensory attributes of Wagyu beef, such as flavor and microbial stability.